Evaluation of laboratory compactive effort on asphaltic concrete mixes - Abdul Sukor, Nur Sabahiah (2005)
Good compaction is the most important factor to consider when constructing asphalt mixture either in the laboratory or in the field. The higher compactive effort presents the higher density to the pavement. The 75 blows as compactive effort in designing laboratory Marshall mixes sample is usually selected. Too high compaction could affect the pavement durability. The aim of this study is to investigate the performance of 50 blows comparing to 75 blows of compactive effort in Marshall Mix Design. The experiment included two types of mixes, ACW14 and ACW20 where 50 and 75 blows were used for each mix. ACW20 samples were tested according to AASHTO T283-89 "Resistance of Compacted Bituminous Mixture to Moisture Induced Damage" and ACW14 samples were tested using Universal Testing Machine according to ASTM D4123 "Standard Test Method for Indirect Tension Test for Resilient Modulus of Bituminous Mixtures." 50 blows compactive effort for ACW20 showed the higher tensile strength ratio when tested for moisture induced damage. For ACW14, the 50 blows compactive effort indicated lower Resilient Modulus than the 75 blows but still above the estimated performance. In general, mixes with 50 blows compactive effort indicated the same performance with the 75 blows samples.